A Literature Review of Social Media for Marketing - Kavak, Bahtışen; Özdemir, Neslişah; Erol-Boyacı, Gülay (IGI Global, 2020)
Digital economy has become a priority for companies and countries since consumer profile and consumption habits have greatly changed. Companies have begun to transfer the services they offer to the Internet. Also, a digital economy creates networks amongst individuals, communities, companies, and markets. With digitalization, not only have consumers' profiles changed, but marketing tools have changed as well. Social media marketing (SMM) is the product of this trend and is marketing through social media channels (SMCs). Therefore, this chapter examines social media use within business-to-consumer (B2C) and business-to-business (B2B) contexts. Moreover, the authors focus on the differences of SMCs adoption in B2C and B2B contexts.